Serum bicarbonate is associated with kidney outcomes in autosomal dominant polycystic kidney disease. Issue 12 (30th December 2020) - Blijdorp, Charles J; Severs, David; Musterd-Bhaggoe, Usha M; Gansevoort, Ronald T; Zietse, Robert; Hoorn, Ewout J; ,
Abstract: Background: Metabolic acidosis accelerates progression of chronic kidney disease, but whether this is also true for autosomal dominant polycystic kidney disease (ADPKD) is unknown. Methods: Patients with ADPKD from the DIPAK (Developing Interventions to halt Progression of ADPKD) trial were included [ n  = 296, estimated glomerular filtration rate (eGFR) 50 ± 11 mL/min/1.73 m 2, 2.5 years follow-up]. Outcomes were worsening kidney function (30% decrease in eGFR or kidney failure), annual eGFR change and height-adjusted total kidney and liver volumes (htTKV and htTLV). Cox and linear regressions were adjusted for prognostic markers for ADPKD [Mayo image class and predicting renal outcomes in ADPKD (PROPKD) scores] and acid–base parameters (urinary ammonium excretion). Results: Patients in the lowest tertile of baseline serum bicarbonate (23.1 ± 1.6 mmol/L) had a significantly greater risk of worsening kidney function [hazard ratio = 2.95, 95% confidence interval (CI) 1.21–7.19] compared with patients in the highest tertile (serum bicarbonate 29.0 ± 1.3 mmol/L). Each mmol/L decrease in serum bicarbonate increased the risk of worsening kidney function by 21% in the fully adjusted model (hazard ratio = 1.21, 95% CI 1.06–1.37). Each mmol/L decrease of serum bicarbonate was also associated with further eGFR decline (−0.12 mL/min/1.73 m 2 /year, 95% CI −0.20 to −0.03). Serum bicarbonate was not associated with changes in htTKV or htTLV growth. Conclusions: In patients with ADPKD, a lower serum bicarbonate within the normal range predicts worse kidney outcomes independent of established prognostic factors for ADPKD and independent of urine ammonium excretion. Serum bicarbonate may add to prognostic models and should be explored as a treatment target in ADPKD. Graphical Abstract: